Mobile Cloud Computing with SOAP and REST Web Services - Ali, Mushtaq; Mohamad Fadli, Zolkipli; Jasni, Mohamad Zain; Shahid, Anwar (IOP Publishing, 2018)
Mobile computing in conjunction with Mobile web services drives a strong approach where the limitations of mobile devices may possibly be tackled. Mobile Web Services are based on two types of technologies; SOAP and REST, which works with the existing protocols to develop Web services. Both the approaches carry their own distinct features, yet to keep the constraint features of mobile devices in mind, the better in two is considered to be the one which minimize the computation and transmission overhead while offloading. The load transferring of mobile device to remote servers for execution called computational offloading. There are numerous approaches to implement computational offloading a viable solution for eradicating the resources constraints of mobile device, yet a dynamic method of computational offloading is always required for a smooth and simple migration of complex tasks. The intention of this work is to present a distinctive approach which may not engage the mobile resources for longer time. The concept of web services utilized in our work to delegate the computational intensive tasks for remote execution. We tested both SOAP Web services approach and REST Web Services for mobile computing. Two parameters considered in our lab experiments to test; Execution Time and Energy Consumption. The results show that RESTful Web services execution is far better than executing the same application by SOAP Web services approach, in terms of execution time and energy consumption. Conducting experiments with the developed prototype matrix multiplication app, REST execution time is about 200% better than SOAP execution approach. In case of energy consumption REST execution is about 250% better than SOAP execution approach.